Distinct functions of soluble guanylyl cyclase isoforms NO-GC1 and NO-GC2 in inflammatory and neuropathic pain processing. Issue 3 (March 2019) - Petersen, Jonas; Mergia, Evanthia; Kennel, Lea; Drees, Oliver; Steubing, Rebecca Dorothee; Real, Catherine Isabell; Kallenborn-Gerhardt, Wiebke; Lu, Ruirui; Friebe, Andreas; Koesling, Doris; Schmidtko, Achim
Abstract : Abstract: A large body of evidence indicates that nitric oxide (NO)/cGMP signaling essentially contributes to the processing of chronic pain. In general, NO-induced cGMP formation is catalyzed by 2 isoforms of guanylyl cyclase, NO-sensitive guanylyl cyclase 1 (NO-GC1) and 2 (NO-GC2). However, the specific functions of the 2 isoforms in pain processing remain elusive. Here, we investigated the distribution of NO-GC1 and NO-GC2 in the spinal cord and dorsal root ganglia, and we characterized the behavior of mice lacking either isoform in animal models of pain. Using immunohistochemistry and in situ hybridization, we demonstrate that both isoforms are localized to interneurons in the spinal dorsal horn with NO-GC1 being enriched in inhibitory interneurons. In dorsal root ganglia, the distribution of NO-GC1 and NO-GC2 is restricted to non-neuronal cells with NO-GC2 being the major isoform in satellite glial cells. Mice lacking NO-GC1 demonstrated reduced hypersensitivity in models of neuropathic pain, whereas their behavior in models of inflammatory pain was normal. By contrast, mice lacking NO-GC2 exhibited increased hypersensitivity in models of inflammatory pain, but their neuropathic pain behavior was unaltered. Cre-mediated deletion of NO-GC1 or NO-GC2 in spinal dorsal horn neurons recapitulated the behavioral phenotypes observed in the global knockout. Together, these results indicate that cGMP produced by NO-GC1 or NO-GC2 in spinal dorsal horn neurons exert distinct, and partly opposing, functions in chronic pain processing. Abstract : The in vivo relevance of the 2 NO-GC isoforms for pain processing was investigated using global and conditional knockout mice.